(untitled) (Revista Iberoamericana de Bioética, 2023)
The content of the fundamental right to privacy has been extended to encompass information as intimate as an individual’s own genes. Emerging scenarios derived from advances in biotechnology and the human genome compel biolaw to regulate, and include in its jurisdiction relevant elements to protect the right to privacy as it pertains to human dignity. This paper describes international conventions and declarations, as well as Costa Rican legislation, that could be applied in the field of predictive genetic testing in oncology.